Evaluation of nursing students' efficacy, attitude, and confidence level in a perioperative setting using virtual‐reality simulation. Issue 6 (31st July 2022) - Siah, Rosalind C. J.; Xu, Ping; Teh, Cheang L.; Kow, Alfred W. C.
Abstract: Aims: This study aimed to evaluate the efficacy, attitude, and level of confidence among nursing students as scrub nurses in a perioperative environment via virtual‐reality simulation. Background: The advantages of virtual reality have been demonstrated to provide a safe and effective mechanism to educate and evaluate students' performances, but the use of virtual reality in perioperative nursing remained limited. Methods: Nineteen sessions were conducted in a room equipped with virtual‐reality headsets and two touch controllers. The surgical workflow of a scrub nurse was developed based on qualitative perspectives from nursing faculties and hospital clinicians working in operating theaters. A survey on the efficacy, attitude, and level of confidence among the participants was conducted after the virtual‐reality simulation. Results: Two hundred and seven nursing students due for their clinical posting in operating theaters completed the evaluation. More than 90% of them indicated "neutral" and above in terms of efficacy, attitude, and confidence level with Cronbach's α values exceeding .90. Conclusions: Virtual reality offers promising potential as an alternative clinical experience to physical simulation for nursing students to increase their efficacy, attitude, and level of confidence as scrub nurses in a perioperative environment through a standardized scenario‐based digital environment.